1990
DOI: 10.1111/j.1432-1033.1990.tb15565.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of lipopolysaccharide‐binding protein from hemolymph of American cockroach Periplaneta americana

Abstract: A protein having affinity to lipopolysaccharide of Escherichia coli K12 was purified to homogeneity from the hemolymph of Periplaneta americana. This protein, with an average molecular mass of 450 kDa, was a homooligomer of a 28‐kDa subunit protein. Comparative studies using lipopolysaccharide molecules of E. coli and Salmonella minnesota suggested that this protein recognizes and binds to a specific carbohydrate structure of E. coli lipopolysaccharide. Ca2+ was required for this protein to bind to lipopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 39 publications
2
46
1
3
Order By: Relevance
“…Recognition-specific proteins have been found in some other insects (Söderhall et al, 1988;Ochiai & Ashida, 1988;Richards et al, 1989;Jomori et al, 1990) and one species of crayfish (Duvic & Söderhall, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition-specific proteins have been found in some other insects (Söderhall et al, 1988;Ochiai & Ashida, 1988;Richards et al, 1989;Jomori et al, 1990) and one species of crayfish (Duvic & Söderhall, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (34) concluded that multiple endogenous serum lectins in the cockroach, Blaberus discoidalis, play important roles in insect innate immunity. Multiple lectins have also been isolated from three other insect species, the American cockroach Periplaneta americana (35)(36)(37)(38), the West Indian leaf cockroach B. discoidalis (34,39,40), and the silkworm B. mori (14,15,(41)(42)(43). In M. sexta, we have identified a family of C-type lectins with different specificities.…”
Section: Binding Of Iml-2 To Lps -A Candidate Ligand For Iml-2 Ismentioning
confidence: 99%
“…LPS is the non-pathogenic, non-living surface molecule derived from E. coli. It is highly immunogenic (Söderhäll 1982;Ratcliffe et al 1985;Jomori et al 1990) and elicits the production of antimicrobial peptides over many hours (Sö derhäll 1982;Ratcliffe et al 1985;Kato et al 1994;Lemaître et al 1996). All injections were made through the pleural membrane between the second and the third abdominal segments, using sterilized glass capillaries that had been pulled out to a fine point.…”
Section: (B) Immune Treatmentsmentioning
confidence: 99%